Oligometastatic Disease and Local Therapies: A Medical Oncology Perspective. Issue 2 (March 2020) - Hafez, Navid; Gettinger, Scott
Abstract : Abstract: Numerous studies in a variety of solid tumor malignancies have demonstrated prolonged progression-free and overall survival with the addition of definitive local therapies to systemic therapies in patients with a limited number of metastases. A subset of patients with oligometastases (1–5 metastases) may experience long-term disease remission or cure after local therapies such as surgery or stereotactic body radiation therapy to metastatic sites. This article reviews the literature in oligometastatic disease and considers a theoretical rationale for a curative approach in a subset of oligometastatic solid tumor patients. In oligometastatic colorectal cancer patients with liver-only metastases and in non–small cell lung cancer patients with disease control after primary therapy and with limited nodal involvement, aggressive local therapies should be considered. Clinical trials and further biomarker validation across disease types are necessary to clarify which subsets of patients may define a theorized "oligometastatic state" and therefore benefit from aggressive local therapies.